Antiglycoxidative properties of amantadine - a systematic review and comprehensive in vitro study - Miłosz Nesterowicz; Małgorzata Żendzian-Piotrowska; Jerzy Robert Ładny; Anna Zalewska; Mateusz Maciejczyk (Taylor & Francis Group, 2023)
An important drug used in the treatment of Parkinson's disease is amantadine. We are the first to perform a comprehensive study based on various glycation and oxidation factors, determining the impact of amantadine on protein glycoxidation. Sugars (glucose, fructose, galactose) and aldehydes (glyoxal, methylglyoxal) were used as glycation agents, and chloramine T was used as an oxidant. Glycoxidation biomarkers in albumin treated with amantadine were generally not different from the control group (glycation/oxidation factors), indicating that the drug did not affect oxidation and glycation processes. Molecular docking analysis did not reveal strong binding sites of amantadine on the bovine serum albumin structure. Although amantadine poorly scavenged hydroxyl radical and hydrogen peroxide, it had significantly lower antioxidant and antiglycation effect than all protein oxidation and glycation inhibitors. In some cases, amantadine even demonstrated glycoxidant, proglycation, and prooxidant properties. In summary, amantadine exhibited weak antioxidant properties and a lack of antiglycation activity.